HUBUNGAN PERSEPSI KELUARGA TERHADAP KOMUNIKASI TERAPEUTIK PERAWAT DENGAN RESILIENSI KELUARGA PASIEN ICU - Lola Shabila Rismayanti (2023)
Family members of critically ill patients face a lot of uncertainty and distress during their close stay in the Intensive Care Unit (ICU). For this reason, nurses must have the ability to apply adequate therapeutic communication techniques to help families adapt and get through difficult situations. This study aims at determining the relationship between nurse therapeutic communication and ICU patients' family resilience. A cross-sectional design was used involving 65 family members of ICU patients. The respondents were selected by way of a purposive sampling technique. Nurses therapeutic communication was investigated using Quality of Communication (QOC) and family resilience using Walsh Family Resilience Questionnaire (WFRQ). The study findings show that nurses therapeutic communication has a significant effect on the family resilience (p < 0.05). For this reason, nurses should improve therapeutic communication for the patient's family so that good communication will gain family resilience